Aprimoramento da estimativa do fluxo luminoso e metodologia de projeto para sistemas de iluminação que utilizam diodos emissores de luz - Chies, Leandro (2016)
The understanding of the interrelationships among the photometrical, electrical and thermal (photo-electro-thermal) parameters is extremely important to design lighting systems based on light-emitting diodes (LEDs), because the LEDs are highly influenced by these conditions. The efficacy and lifespan of an LED system that uses even the best LEDs, commercially available, will be only a fraction of what it would be if the electrical, thermal and optical design is poorly designed. This work proposes an improvement in the estimative of the luminous flux using photo-electro-thermal parameters, without needing any laboratory test. When designing an LED lighting system, it is possible to get almost identical results in terms of luminous flux, luminous efficacy and lifetime by scaling the parameters: intensity of the LED current, the amount of LEDs and the system design cooling. Therefore, a design methodology for LED lighting systems is also proposed. This methodology provides the creation of a design space where the designer can directly identify: the value of the luminous efficacy, thermal resistance of the heatsink and junction temperature when varying the number of LEDs and the direct current, without performing any laboratory testing or using some simulation software with high computational cost. Thus, the designer can set the initial design faster and relate it to the costs involved. Experimental tests were performed in order to validate the proposed design methodology.